Studi pengembangan bakat remaja melalui program mentoring islami - Budi, Setyo; Sastra, Akhmad; Rahman, Imas Kania (Tawazun: Jurnal Pendidikan Islam, 2024)
Every teenager has different talents. The difference does not always lie in the type, but also in the degree or level of possession of a particular talent. Unfortunately, teenagers' talents are not always displayed in real achievements due to various reasons. Among them are due to environmental factors such as the absence of opportunities, infrastructure, support from parents, teachers, family economic level, and location of residence. The purpose of the research is to analyze the development of adolescent talent through the Islamic mentoring program. To be able to develop talent well, a teenager needs the right environment, family support, reliable mentors, and a program that can accommodate his needs. This research uses a library research approach. Data sources come from field surveys, books and various research journals on Islamic education and talent development from the works of scholars, education experts, and mentors. Talent development is an important and main agenda in the adolescent phase. Talent development of adolescents requires support from various parties. The world of education supports talent development programs as seen from the survey results as many as 69.6% of schools already have talent development programs. Of the schools that already have a talent development program, 78.9% have not implemented the talent development program optimally. There is no Islamic mentoring program that has a portion of talent development for adolescents in its program content. Abstrak Setiap remaja mempunyai bakat yang berbeda-beda. Perbedaan tidak selalu terletak pada jenis, tetapi juga pada derajat atau tingkat pemilikan bakat tertentu. Sayang sekali bahwa bakat remaja tidak selalu tertampil dalam prestasi yang nyata karena berbagai macam sebab. Diantaranya karena faktor lingkungan seperti ketiadaan kesempatan, sarana prasarana, dukungan orangtua, guru, taraf ekonomi keluarga, juga lokasi tinggal. Tujuan penelitian adalah menganalisa pengembangan bakat remaja melalui program mentoring islami. Untuk dapat mengembangkan bakat dengan baik, seorang remaja membutuhkan lingkungan yang tepat, dukungan keluarga, mentor handal, dan program yang mampu mewadahi kebutuhanya. Penelitian ini menggunakan pendekatan kepustakaan (library research). Sumber data yang berasal dari survey lapang, buku-buku dan berbagai jurnal penelitian tentang pendidikan islami dan pengembangan bakat dari karya para ulama, ahli pendidikan, dan mentor. Pengembangan bakat menjadi agenda penting dan utama pada fase remaja. Pengembangan bakat remaja membutuhkan dukungan dari berbagai pihak. Dunia pendidikan mendukung program pengembangan bakat yang terlihat dari hasil survey sebanyak 69,6 % sekolah sudah memiliki program pengembangan bakat. Dari sekolah yang sudah memiliki program pengembangan bakat tersebut sebanyak sebanyak 78,9 % belum melaksanakan program pengembangan bakat secara optimal. Belum ada program mentoring islami yang memiliki porsi pengembangan bakat bagi remaja dalam konten programnya.